Soluble activin receptor type IIB treatment does not cause fat loss in mice with diet-induced obesity - McPherron, Alexandra C. (2011)
The growth factor myostatin (MSTN) negatively regulates skeletal muscle mass. Mstn gene deletion in mice causes increased muscle mass, reduced adiposity and resistance to genetic or diet-induced obesity. Pharmacologic MSTN inhibition in mice also causes increased muscle mass and resistance to diet-induced obesity. To test whether MSTN inhibition causes weight loss in mice that are already obese, we inhibited MSTN in mice fed a high-fat diet. Mice were fed a diet containing 60% kcal from fat for 12 weeks followed by treatment with a soluble MSTN receptor derived from the activin receptor type IIB extracellular domain. During the next 12 weeks of soluble receptor treatment and high-fat diet feeding, lean mass increased without a loss of adipose mass. Glucose metabolism was also similar between groups. Our results suggest that MSTN inhibition may be ineffective at inducing weight loss in obese patients.